In the field: Listening to Adaptation Pioneers - Habermann, Birgit; Kiptoo, Emmaculate; Gichuki, Leah (International Livestock Research Institute, 2024)
Field days are events that bring people together. In this case, adaptation pioneers, other farmers, different partners, researchers – and everybody wants to share or learn something. The atmosphere is fascinating: there is all this anticipation and excitement in the air, especially with the dark clouds looming over the farms in this rainy May. When we arrive in the morning on the farm, the tents are being erected. The team set up the registration table, puts up the banners, and prepares the disinfectant for people to step in to prevent the transmission of livestock diseases.